2006
DOI: 10.1089/met.2006.4.113
|View full text |Cite
|
Sign up to set email alerts
|

Mild Gestational Hyperglycemia and the Metabolic Syndrome in Later Life

Abstract: Women who failed the OGCT, but not the OGTT, showed a subsequent worse metabolic pattern than pNGT subjects, independently of confounding factors. In the presence of obesity, the prevalence of the metabolic syndrome was similar to that of obese pGDM women, and almost twofold higher than in obese pNGT controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…Previous studies have reported high rates of the metabolic syndrome in women with a history of GDM (11,12,(25)(26)(27)(28). Indeed, at median 9.8 yr postpartum, the prevalence of metabolic syndrome (by World Health Organization criteria) was 38.4% in Danish women with previous GDM, compared with 13.4% in their peers (11).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have reported high rates of the metabolic syndrome in women with a history of GDM (11,12,(25)(26)(27)(28). Indeed, at median 9.8 yr postpartum, the prevalence of metabolic syndrome (by World Health Organization criteria) was 38.4% in Danish women with previous GDM, compared with 13.4% in their peers (11).…”
Section: Discussionmentioning
confidence: 95%
“…This risk is 10 times higher in women with concomitant pre-pregnancy obesity (Bo et al, 2004a). Thus, even mild gestational hyperglycemia predicts metabolic syndrome (Bo et al, 2004b), and metabolic syndrome is increasingly more likely to develop over time following the index pregnancy (Bo et al, 2006). These studies highlight the chronic nature of the metabolic dysfunction associated with GDM.…”
Section: Development Of Metabolic Syndrome After Gdmmentioning
confidence: 96%
“…Gestational diabetes mellitus (GDM), a form of glucose intolerance diagnosed during pregnancy, affects more than 200,000 women each year in the United States or about 7% of all pregnant women (American Diabetes Association [ADA], ). Gestational diabetes mellitus is considered a unique metabolic syndrome risk factor in women (Bentley‐Lewis, Koruda, & Seely, ; Bo et al, ; Retnakaran et al, ; Vohr & Boney, ), indicating increased risk for type 2 diabetes and CVD (Alberti et al, ) and the need for early risk factor surveillance in this population. In general, women with previous GDM have a 20% to 50% chance of developing type 2 diabetes in the next 5 to 10 years (ADA), whereas cumulative incidence has been reported as high as 70% among American Indian women with previous GDM (Kim, Newton, & Knopp, ).…”
mentioning
confidence: 99%